Key Performance Indicator Analysis In Improving The Quality Of Excellent Service On Globalxtreme Companies - Bagus Kusuma Wijaya; I Dewa Ayu Agung Tantri Pramawati; Abdul Samad Arief; Mustika Wati Alfia Ningtyas; Umi Juniyarti (Institute of Computer Science (IOCS), 2022)
In line with the development of technology and information in Indonesia is multiplying. Competition between companies is getting tougher. A policy base can satisfy customers' wishes to anticipate competition in a company's plans. With the intense competition between competitors, a company needs to have good quality in service by satisfying customer needs which can be an advantage in the competition. Companies need measurement because it is an essential tool that supports companies in measuring company performance that is easy to visualize. One company that uses KPI as a Service Standard is GlobalXtreme Bali Branch. GlobalXtreme Bali Branch is a company engaged in technology and IT by providing internet services in several areas in Bali. With this, we need a benchmark that can be used as a benchmark for company performance in achieving this service excellence goal, one of which is a Key Performance Indicator (KPI) in helping a company determine the success or failure of an agency in achieving the targets that have been set. In this study, from the use of KPI calculations, it is known that indicators or processes with Audit Values ??which include Observation, FCR, Knowledge Test and Reactivation and the Customer Service Team, must achieve good Revenue Targets and CSAT. From the beginning, the KPI target became an evaluation material for the company, especially the customer service team, to improve customer service to achieve the KPI target. This result is an evaluation for superiors in the company regarding performance, teamwork, and initiative.